Identification, characterization and molecular adaptation of class I redox systems for the production of hydroxylated diterpenoids. Issue 1 (December 2016) - Görner, Christian; Schrepfer, Patrick; Redai, Veronika; Wallrapp, Frank; Loll, Bernhard; Eisenreich, Wolfgang; Haslbeck, Martin; Brück, Thomas
Abstract Background De novo production of multi-hydroxylated diterpenoids is challenging due to the lack of efficient redox systems. Results In this study a new reductase/ferredoxin system fromStreptomyces afghaniensis (AfR·Afx) was identified, which allowed theEscherichia coli -based production of the trihydroxylated diterpene cyclooctatin, a potent inhibitor of human lysophospholipase. This production system provides a 43-fold increase in cyclooctatin yield (15 mg/L) compared to the native producer. AfR·Afx is superior in activating the cylcooctatin-specific class I P450s CotB3/CotB4 compared to the conventionalPseudomonas putida derived PdR·Pdx model. To enhance the activity of the PdR·Pdx system, the molecular basis for these activity differences, was examined by molecular engineering. Conclusion We demonstrate that redox system engineering can boost and harmonize the catalytic efficiency of class I hydroxylase enzyme cascades. Enhancing CotB3/CotB4 activities also provided for identification of CotB3 substrate promiscuity and sinularcasbane D production, a functionalized diterpenoid originally isolated from the soft coralSinularia sp.